Fruit development,postharvest handling and product development studies in red banana(musa AAA group) - Geetha Lekshmi P R (Department of Processing Technology, College of Agriculture, 2005)
The present investigation was carried out at the Department of Processing Technology, College of Agriculture, Vellayani during 2003-2005 with the objective to study the fruit development in Red Banana, development of a grading system, postharvest handling and product development studies of Red Banana. For the fruit development studies, Red Banana plants were selected and tagged at the time of bunch emergence (opening of the first hand) to ensure the selection of fruits with uniform chronological age. At each sampling, fingers from the second hand of five bunches were harvested at 4,6,8,10,12,14 and 15 weeks after bunch emergence and at harvest (16 weeks) and were subjected to various physical and chemical analysis. Consumer preference according to the physical characters of hands and fingers was evaluated and grades for Red Banana hands were suggested. Various prepackaging and packing treatments were used to assess the mechanical damage caused due to transportation. Postharvest storage and ripening studies were conducted using prepackaging treatments and different storage temperatures. In the product development studies, standardization of pectinase enzyme treatment for the clarification of Red Banana juice with different enzyme concentration, incubation temperature and duration was done. Red Banana squash and RTS were prepared from this clarified juice and their storage stability and preference were determined. Bottling of ripe Red Banana fruits was conducted using different concentration of sugar and acidity of canning medium. Fruit development studies revealed that Red Banana reached its full maturity at 16 weeks after the bunch emergence and it can be harvested with optimum maturity at 15 weeks after the bunch emergence. Consumer preference study revealed that medium sized hands are mostly preferred. Grades are suggested for Red Banana hands as grading ensure the quality and thus fetches higher price. For export and long distance market, hands of Grade A and B could be suggested, Grade B and C could be proposed for dessert purpose in local and distant market. Grade D lacked market appeal and could be used for processing into banana products. Transportation studies showed that prepackaging of bananas significantly reduced bruises on the fruits. Prepackaging of Red Banana with vented polyethylene bags with or with out ethylene absorbent and the storage temperature of 16 ºC was found best for the storage. Prepackaging with ethylene absorbent recorded an additive effect in extending the green life of fruits. Enzyme clarification of Red Banana pulp with 0.50 per cent pectinase enzyme at 40 ºC for four hours was found the best for juice yield. Red Banana squash prepared from the clarified juice was stored well for a period of 120 days. Red Banana RTS prepared using 15 per cent juice, 12 ºB TSS and 0.15 per cent acidity recorded the highest organoleptic score among the different RTS formulations. RTS recorded a shelf life of 60 days at ambient temperature. It was observed that Red Banana squash and RTS had a good consumer acceptance. Of the various concentrations tried for canning medium for bottling of the ripe Red Banana fruits showed that the treatment using syrup of 30 ºB and 0.10 per cent acidity was better and products stored well for a period of 45 days.